A safeguard mechanism regulates Rho GTPases to coordinate cytokinesis with the establishment of cell polarity - Meitinger, Franz; Pereira, Gislene (PLoS biology, 2013)
Gps1 provides a novel molecular polarity cue at the cell division site that guides Rho1- and Cdc42-dependent polarization during and after cytokinesis in budding yeast.